Sir John Prise and His Books: Manuscript Culture in the March of Wales. (1st June 2022) - Fulton, Helen
Sir John Prise (1501/2–55) was a Welsh lawyer and book collector who was one of the royal commissioners responsible for closing down the monasteries at the Dissolution of the 1530s. Operating mainly in the March of Wales, Prise was able to save around 100 medieval manuscripts which would otherwise have been destroyed. As a Welsh speaker, Prise was keenly interested in medieval Welsh writing and some of the most famous medieval Welsh manuscripts passed through his hands. He was particularly interested in the British history of Geoffrey of Monmouth and in his Latin prose treatise, Historiae Britannicae Defensio, published in 1573 after his death, Prise put forward a spirited defence of the 'British history' related by Geoffrey, based almost entirely on his reading of manuscripts that he owned. This article examines the significance of Sir John Prise, his writing and his book collection in relation to the transmission of medieval texts into the Tudor age.